Analisis Pelanggaran Etika Pemasaran pada Perusahaan Mie Instan: Ketidaksesuaian Produk dengan Klaim pada Iklan - Amelia Fega; Halimah Zahrah; Ahmad Khairi; Muhammad Fadhlan Rizqullah; Alfathir Hilal Nazmi (INDO PUBLISHING, 2025)
Marketing strategies play a crucial role in shaping consumer perceptions and trust toward a product. However, marketing practices that do not reflect the actual quality or characteristics of a product may violate business ethics and harm consumers. This study aims to analyze the discrepancy between advertising claims and the reality of instant noodle products, as well as to identify forms of ethical violations in marketing practices. The method used is a case study with a qualitative approach based on literature review. The findings reveal that marketing strategies emphasizing hyperbolic claims without supporting evidence can diminish consumer trust and violate the Indonesian Advertising Ethics Code (Etika Pariwara Indonesia – EPI) and the Consumer Protection Act (Undang-Undang Perlindungan Konsumen – UUPK). This study also found that social media strengthens the role of consumers as ethical watchdogs, making brand reputations more vulnerable to misleading claims.